The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/pam.10152
|View full text |Cite
|
Sign up to set email alerts
|

Child protective intervention in the context of welfare reform: The effects of work and welfare on maltreatment reports

Abstract: Recent changes in welfare policy have produced changes in parental work and welfare receipt. These factors are assessed in relation to investigated reports of child abuse and neglect using survey data on 1998 welfare recipients in nine Illinois counties, in conjunction with longitudinal administrative data on cash welfare benefits, employment, and child abuse and neglect reports. Trend analyses show that rates of child maltreatment reports among welfare recipients have risen since the passage of PRWORA in 1996… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 26 publications
4
45
1
Order By: Relevance
“…These results are consistent with other studies (Courtney et al, 2001;Slack et al, 2003) and suggest that parents with seriously troubled pasts and/or ongoing family or neighborhood stressors may be more likely to have more severe difficulties with their children and thus may be more likely to have their case investigated and opened.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are consistent with other studies (Courtney et al, 2001;Slack et al, 2003) and suggest that parents with seriously troubled pasts and/or ongoing family or neighborhood stressors may be more likely to have more severe difficulties with their children and thus may be more likely to have their case investigated and opened.…”
Section: Discussionsupporting
confidence: 92%
“…African American recipients were less likely to be investigated and supervised by CPS than Whites when other factors were held constant. This finding is consistent with previous studies of welfare populations where African American welfare recipients are less likely to be involved with CPS than their White counterparts (Goerge & Lee, 2000;Needell et al, 1999;Slack et al, 2003). In addition to race, low income-to-needs ratio, cohabitation, childhood welfare receipt, or having a learning disability were significantly and positively related to one's chances of being reported to CPS.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Paxson and Waldfogel [83] in a large study found that an increase from 10% to 15% of children living in extreme poverty was associated with a 22% increase in child abuse. Many others have found similar results [84]. However, interpreting these findings in decision-making contexts requires careful examination: "The experiences of those trying to parent in a profoundly unequal society are not interrogated rigorously enough in current responses, with causation and correlation confused in a highly abstract language that renders real people and their lives invisible and/or unintelligible" ( [41], p. 5).…”
Section: Inequality and Povertymentioning
confidence: 99%